Assessing the efficacy of a workplace violence educational model for nursing professionals: A prototype model - Putra, Ardia; Kamil, Hajjul; Adam, Muhammad; Usman, Said; Rauzatul Jannah, Syarifah; Abdurrahman, Abdurrahman (Acta Biomedica Atenei Parmensis, 2025)
Background and aim of the work: Violence directed towards nurses resembles the iceberg phenomenon, wherein numerous incidents remain unreported. A predominant factor contributing to this underreporting is that the victims are required to report such incidents and often lack familiarity with their organization's internal reporting protocols. The study aims to assess the efficacy of the STOP Workplace Violence Educational Model during the preliminary testing and implementation stages among nurses working in healthcare facilities within Aceh Province in Indonesia.Materials and methods: The researcher used a research-and-development design to create the STOP Workplace Violence Educational Model for nurses in Aceh Province. Its efficacy was assessed via a questionnaire evaluating content, media eligibility, ease of use, and user expectations. In the preliminary testing phase, 11 evaluators participated. During implementation, small-scale socialization (n=90) and nurse evaluations occurred. Data analysis focused on central tendency measures: mean, standard deviation, and min-max values.Results: The STOP Workplace Violence Educational Model underwent rigorous evaluation, yielding highly favorable outcomes across key dimensions. Preliminary testing by the evaluator team achieved “Excellent” ratings (Min-Max: 3-4; M=3.84±0.21), while assessments of user expectations and implementation also received “Excellent” scores (Min-Max: 3-4; M=3.67±0.34). Content/Material was rated highly (M=3.69±0.40) for relevance and comprehensiveness, Media Eligibility scored well for technical quality and accessibility (M=3.60± 0.38), and Ease of Use excelled (M=3.72±0.35) due to intuitive design. User expectations (M=3.74±0.32) further affirmed the model’s effectiveness in addressing workplace violence in healthcare settings.Conclusions: The web-based STOP Workplace Violence Educational Model application successfully provided valuable information to nurses, enhancing their understanding of workplace violence incidents in hospital settings. This application demonstrated its potential to positively influence nurses’ self-efficacy, improving their competencies, including knowledge, psychomotor skills, and attitudes. (www.actabiomedica.it).